Seasonal dynamics of non-structural carbohydrates in the storage organs of saffron (Crocus sativus L.) - Mzabri Ibtissam; Boulida Zaineb; Mesbahi Qamar; Chkird Fadoua; Alla Anass; Arabi Mourad; Kouddane Noureddine; Berrichi Abdelbasset (E3S Web of Conferences)
Seasonal dynamics of total nonstructural carbohydrates (NSC) were investigated in Crocus sativus L. over 12-month period. This study offers novel insights into the temporal patterns of carbohydrate storage and mobilization, emphasizing critical phases of reserve accumulation and depletion that are integral to the plant’s growth and dormancy cycles. Monthly sampling was conducted, and NSC concentrations in storage organs were quantified. The results revealed a characteristic 'V'-shaped temporal profile, with peak NSC levels observed at the onset of the growth cycle (September) and at the beginning of the vegetative dormancy period (April) , while the lowest concentrations were recorded during the active vegetative phase (December– January). Qualitative analysis via thin layer chromatography (TLC) identified fructose, glucose, maltose, and xylose as the predominant carbohydrate reserves accumulated within the storage organs. Elucidation of these seasonal carbohydrate dynamics provides valuable information for optimizing cultivation strategies and enhancing saffron yield.